A scratch resistant yet healable automotive clearcoat containing hyperbranched polymer and POSS nanostructures. Issue 79 (11th August 2016) - Yari, H.; Mohseni, M.; Messori, M.
Abstract : In this paper a typical acrylic melamine clearcoat has been modified with hyperbranched polymer and polyhedral oligomeric silsesquioxane nanostructures to simultaneously enhance its scratch resistance and healing ability. Abstract : In this paper a typical acrylic melamine clearcoat has been modified with hyperbranched polymer and polyhedral oligomeric silsesquioxane nanostructures to simultaneously enhance its scratch resistance and healing ability. Scratch behaviour and healing performance of clearcoats were investigated by micro-scratching and confocal profilometry techniques. Various techniques were employed to correlate scratch resistance and healing enhancements to the various mechanical and structural characteristics of nano clearcoats. Enhanced scratch resistance was attributed to the increased elastic recovery of the clearcoats in the presence of nano-structured modifiers. In addition, the improved self-healing performance was assigned to the partial replacement of covalent cross-links with physical ones i.e. H-bonding. Simultaneous reinforcement with covalent and physical linkages led to the formation of a more flexible network which maintains its mechanical integrity at ambient temperature and also provides dynamic chain movements for thermal healing treatments at high temperature.